2007
DOI: 10.1373/clinchem.2007.085506
|View full text |Cite
|
Sign up to set email alerts
|

An N-Terminal Molecular Form of Parathyroid Hormone (PTH) Distinct from hPTH(1–84) Is Overproduced in Parathyroid Carcinoma

Abstract: Background:A new parathyroid hormone (PTH) species, the N-terminal PTH form (N-PTH), is distinct from intact human PTH of 84 amino acid residues [hPTH(1-84)] and is recognized in a 3rd-generation assay of "whole" PTH (wPTH; the 1-2 epitope) but not in a 2nd-generation assay of "total" PTH (tPTH; the 12-18 epitope). N-PTH usually represents <15% of wPTH but can be overproduced in severe primary hyperparathyroidism (PHPT) and secondary hyperparathyroidism. We investigated whether N-PTH is also overproduced in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 11 publications
5
66
1
2
Order By: Relevance
“…In the group 1 patients, PTH values decreased after surgery and were then lower when measured with the third-generation than with the secondgeneration PTH assays regardless of the assay used, as described previously (10 ). Our data and those reported previously (9,10 ) are consistent with the presence of a PTH molecule in some patients that is produced in excessive amounts by a parathyroid adenoma or carcinoma and regresses after parathyroidectomy, as shown in our study and by Räkel et al (10 ), or persists for the duration of a 12-month treatment with a calcimimetic agent (9 ). D'Amour et al (12 ) used HPLC to identify a new PTH form, amino PTH (N-PTH), which is distinct from PTH(1-84) and is overproduced in primary and secondary hyperparathyroidism.…”
Section: © 2006 American Association For Clinical Chemistrysupporting
confidence: 87%
See 1 more Smart Citation
“…In the group 1 patients, PTH values decreased after surgery and were then lower when measured with the third-generation than with the secondgeneration PTH assays regardless of the assay used, as described previously (10 ). Our data and those reported previously (9,10 ) are consistent with the presence of a PTH molecule in some patients that is produced in excessive amounts by a parathyroid adenoma or carcinoma and regresses after parathyroidectomy, as shown in our study and by Räkel et al (10 ), or persists for the duration of a 12-month treatment with a calcimimetic agent (9 ). D'Amour et al (12 ) used HPLC to identify a new PTH form, amino PTH (N-PTH), which is distinct from PTH(1-84) and is overproduced in primary and secondary hyperparathyroidism.…”
Section: © 2006 American Association For Clinical Chemistrysupporting
confidence: 87%
“…We and others have demonstrated that subclinical atherosclerosis (4 ) and clinical coronary heart disease (CHD) (5)(6)(7)(8)(9) are associated with higher concentrations of circulating ox-LDL. Recently, we showed, in older adults in the Health, Aging, and Body Composition (Health ABC) cohort (10 ), that high CHD risk status (based on Framingham score) before…”
mentioning
confidence: 99%
“…In contrast, for others, (9,10,13) this ratio stays for whole PTH/iPTH. In the exceptional cases in which the PTH-(1-84) level is paradoxically higher than that of iPTH, it is obvious that one cannot calculate PTH- as the difference between iPTH and PTH-(1-84), because this would yield a negative value.…”
mentioning
confidence: 79%
“…Third generation PTH assays are specific for the 1-84 PTH and do not cross-react with the C-terminal fragments, but they cross-react with a N-terminal molecular form of PTH (amino-PTH), a PTH phosphorylated on the serine in position 17, overproduced in parathyroid carcinoma [12,13] and in rare cases of severe primary hyperparathyroidism [14]. These assays are not as used as the "intact" PTH ones, since two manufacturers only (namely DiaSorin and Roche) present an automated version of these assays, even not available in every country.…”
Section: Pth Determinationmentioning
confidence: 99%